Video-assisted thoracoscopic thymectomy for thymoma: a single-center experience. (March 2018) - Nguyen, Giang Truong; Nguyen, Trung Ngoc; Nguyen, Nam Van; Nguyen, Kien Trung; Le, Anh Viet
Background: Thymoma is a primary tumor derived from the epithelial cells of the thymus, which is commonly seen in the mediastinum. Surgical thymectomy is the radical treatment for thymoma. The recent introduction of video-assisted thoracoscopic surgery has improved the quality of thymectomy surgery. The clinical characteristics of thymoma and the outcomes of video-assisted thoracoscopic thymectomy in Vietnamese patients are still lacking. The objectives of this study were to investigate the clinical and laboratory characteristics of thymoma and to evaluate the early results of video-assisted thoracoscopic thymectomy for thymoma in Vietnamese patients. Methods: All 53 thymoma patients with or without myasthenia gravis who underwent video-assisted thoracoscopic thymectomy in Military Hospital 103, Vietnam, from October 2013 to July 2017 were included. Results: The mean age was 46.5 7.1 years, and the female/male ratio was 1.2:1. Myasthenia gravis, mostly stage IIA, was present in 84.9% of patients. There was no hospital mortality or major postoperative complication. The mean operative time was 65 min, intensive care unit stay was 22 ± 5 h, and postoperative hospital stay was 7.5 ± 1.7 days. Conclusion: Thoracoscopic thymectomy for thymoma in Vietnamese patients achieved improved cosmesis and was safe for both non-myasthenia gravis and myasthenia gravis patients.